Role Of Digital Media In Mass Communication And Its Impact On Society (Trinity Journal of Management, IT & Media (TJMITM), 2016)
The emerging drift in contemporary media scenario has witnessed a  transition in the way information, ideas; opinions are transmitted, shared,  exchanged and interchanged. The sustainable change in media landscape  has remarkably changed the eco system of information delivery, leading  newspapers and news channel are taking to digital journalism in a big  way. The speedy technical progress, which print media is adapting to  continue, has brought about far reaching changes in the modern media  set-up. The onslaught of technology is changing the dynamics of news  delivery too, newspaper once the medium for breaking news, surrendered  that role to TV and internet could take it over. This paper tries to describe  how crudely the news eco system is shifting and it presently looks like the Net breaks the news, TV is doing the follow ups and live coverage  and newspapers end up doing analyses. Digital media gives access  of information at the touch of a mouse bottom. In an interdependent  world, Digital media is making worldwide communication a reality. The  worldwide web is a challenge to traditional news practices because of  its interactive opportunity that offers for instant communication and is  competing ahead at a Remarkable speed, irrespective of any demography  or geographical boundary. This paper attempts to explain that digital  Media has brought the world closer globally. Among the information  revolution, Digital media has become such an integral part of our lives  and plays impactful role in society.
Keywords: Digital Journalism; Contemporary; onslaught technology; Communication; interactive